Face bows in the production of michigan occlusal splints - Gámez-C., Jesús; Dib-K., Alejandro; Espinosa-de S., Irene Aurora (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: Michigan occlusal splints (MOS) are frequently used for the management of patients with bruxism. The literature mentions the use of face bows for mounting models in semi-adjustable articulators, but its benefit in the production of MOS is still controversial. Therefore, the objective of this study was to compare the record of number of contact points and mounting time between MOS made with and without face bows in patients diagnosed with bruxism. Methods: a total of 90 splints were made and distributed among 45 patients diagnosed with bruxism at the Oral Rehabilitation Clinic of Benemérita Universidad Autónoma de Puebla (BUAP). The two splints (one made with a face bow mounted model and the other one without it) were compared at the articulator and clinically. The number of obtained contact points was recorded in both splints as well as the time needed for mounting. The comparisons were made with Wilcoxon statistical test and a significance level lower than 0.05. Results: the splints with face bows showed a greater average of contact points in the mouth (11.67) compared with the ones without face bows (11.58), with no significant difference (p = 0.799). Mounting time was higher in the splints made without face bows (51 s) compared with the ones with face bows (33 s), with no significant difference (p = 0.332). Conclusion: there are no significant differences in using face bows for developing MOS in bruxism patients.